Post-COVID-19 and higher education (Journal of Applied Learning and Teaching, 2022)
The COVID-19 pandemic is a perfect storm to encourage higher education institutions (HEIs) to think differently, to price in risk and review their purpose of existence. This paper examines two thoughts as HEIs transition to a new normal life with COVID-19 – the first relates to the future of online education in higher education and the second pertains to the relevancy of degrees. It argues that transition to any model of cognition and enquiry, including online delivery of courses, needs careful consideration, and must be weighted with its limitation. Academic credentials serve as the foundation to determine if a decision is worth embarking. Devoting resources to strengthening the credentials of higher education qualifications will be essential in the post COVID period. For one, universities need to know that student centricity does not mean that the customer is always right in every aspect. Stepping up the effort to ensure that university degrees remain relevant will be one of the most significant challenges HEIs have to work on.